The Cost of Aggressive Sovereign Debt Policies : How Much is theprivate Sector Affected? - Trebesch, Christoph (IMF Working Papers; Working Paper ;, 2009)
This paper proposes a new empirical measure of cooperative versus conflictual crisis resolution following sovereign default and debt distress. The index of government coerciveness is presented as a proxy for excusable versus inexcusable default behaviour and used to evaluate the costs of default for the domestic private sector, in particular its access to international debt markets. Our findings indicate that unilateral, aggressive sovereign debt policies lead to a strong decline in corporate access to external finance (loans and bond issuance). We conclude that coercive government actions towards external creditors can have strong signalling effects with negative spillovers on domestic firms. "Good faith" debt renegotiations may be crucial to minimize the domestic costs of sovereign defaults.